Post translational Modifications and Protein-Protein Interactome of Endemic Pemphigus in El Bagre, Colombia: A New Variant Analysis - Ana Maria Abreu Velez; Mariana Ramirez-Posada; Michael S Howard (Dermatology Practical & Conceptual)
Background: A new variant of endemic pemphigus foliaceus, El Bagre-EPF, is an orphan autoimmune disease occurring in El Bagre and neighboring municipalities in Colombia, South America.